Pengaruh Jam Kerja, Upah Dan Usia Terhadap Produktivitas Kerja Karyawan PT. Putra Fajar Jaya Medan - Lubis, Yusniar (Universitas Medan Area, 2014)
This study aimed to determine the effect of working hours, wages and age on employee productivity PT. Putra Fajar Jaya, Medan. The number of samples in this study as many as 35 samples. Data was analyzed using multiple linear regression. The results showed that simultaneously working hours, wages and age have a significant effect on employee productivity. Partially hours and wages have a significant effect on employee productivity, whereas age was not a significant effect on employee productivity. Working hours have a greater influence on work productivity compared with wages. Keywords: working hours, wages, age and productivity